Distal Metatarsal Metaphyseal Osteotomy (DMMO) for lesser toe metatarsalgia: a case series of 195 osteotomies - Gabriel Ferraz Ferreira; Hussein Nasser Fares; Vinícius Oliveira; Gustavo Araujo Nunes; Augusto César Bravin; Miguel Viana Pereira Filho (Journal of the Foot & Ankle, 2022)
Objective: The aim of the study was to radiographically evaluate the result of this minimally invasive technique for the surgical treatment of metatarsalgia. Methods: Radiographic images of 195 osteotomies in 48 patients (65 feet) who were exclusively submitted to the Distal Metatalsal Metaphyseal Osteotomy (DMMO) technique in the central rays (second, third, and fourth metatarsals) with a minimum follow-up of six months were analyzed. Bone healing, metatarsal shortening, and bone healing positioning (central, lateral, or medial) were evaluated. All statistical analysis was performed using the R software, and Wilcoxon statistical tests and Student’s t-test paired for continuous variables were used. Results: The mean length of the second metatarsal reduced 7.0mm (p<0.001), the third 6.8mm (p<0.001), and the fourth 6.6mm (p<0.001). In only one case, there was no bone consolidation (second metatarsal). Most osteotomies were consolidated in a central position of the distal fragment. Conclusion: DMMO showed a high rate of bone healing (99.5%), metatarsal shortening, and consolidation in the central position of the distal fragment when performed in the surgical treatment of metatarsalgia. Level of Evidence IV; Case Series.